Defining the ideal public space: A perspective from the publicness - Juan Li; Anrong Dang; Yan Song (Journal of Urban Management, 2022)
The concept of public space can be variously defined and understood from diversified perspectives. However, no matter which definition may be used, the most fundamental character of the public space is its publicness. This paper reviews the definitions and dimensions of publicness from both theoretical and empirical perspectives, and concludes four synthesized dimensions of publicness: ownership, accessibility, management, and inclusiveness. By clarifying the concept of publicness, we can unify the multiple values and functions pertaining to urban public space. The four dimensions are further related to the legal sense and lived sense to interpret public space, respectively. By discriminating their difference, the lived sense corresponding to the dimensions of accessibility, management and inclusiveness, is adopted to define the ideal public space from the perspective of publicness. The proposed definition shows both theoretical and practical significance for urban planning and management.
Keywords: 710; Ideal definition; Lived sense; Multidimensional nature; Public space; Publicness